Acute effects of mango leaf extract on cognitive function in healthy adults: a randomised, double-blind, placebo-controlled crossover study - Dodd, Fiona L.; Kennedy, David O.; Johnson, Jodee; Haworth, Emily; Greener, Jessica P.; Jackson, Philippa A. (Frontiers in Nutrition, 2024)
Extracts made from the leaves of the edible mango plant (Mangifera indica L., Anacardiaceae) have a long history of medicinal usage, most likely due to particularly high levels of the polyphenol mangiferin. Previous research has demonstrated that mango leaf extract (MLE) can beneficially modulate cognitive function in both animals and humans. This study aimed to assess the effects of an acute dose of 300 mg MLE (standardised to contain ≥60% mangiferin) on cognitive performance and mood in healthy adults. In this double-blind, placebo controlled, crossover study, 114 healthy male and female participants (18-43 years) received either MLE or a matched placebo at each testing visit (separated by at least 7 days). Cognitive performance (including the cognitive demand battery) and mood were measured at 30-, 180- and 300-minutes post-dose. The results showed that compared to placebo, MLE had a significant increase in serial 3s and serial 7s subtraction errors overall. There were no other significant effects on cognitive performance. The results of the current study suggest that consumption of 300 mg MLE, in the absence of an observed multi-tasking psychological stressor, does not improve cognitive performance or mood, at up to 300 minutes post-dose. Due to the very limited nature of the effects and since they were observed amongst many analyses, these findings should be considered with caution. The trial is registered at ClinicalTrials.gov (NCT05182450).